Efektivitas Pemberian Aroma Lavender Terhadap Intensitas Nyeri Persalinan : Systematic Literature Review - Nevi Susianty; Nova Avianti Rahayu (Fakultas MIPA dan Kesehatan, Universitas Muhammadiyah Riau, 2021)
Labor pain is part of the normal process, but labor pain is considered the most unwanted and unpleasant aspect of the birthing experience. The aroma of lavender flowers is an aromatherapy which has the main ingredients linaly acetan and linalool. Inhaling the scent of lavender can cause alpha waves in our brain to increase and these waves will help relax our minds. The purpose of this study was to find evidence based on the effectiveness of giving lavender aroma to the intensity of labor pain. This research method uses a systematic literature review approach and there are eight stages used in this review, namely identifying midwifery problems, priority problems and research questions, primary and secondary data frameworks, identification of relevant studies, prism flow diagrams, critical appraisal, data analysis and extraction. data. This review uses 2 databases with a period from 2010-2020. The total articles obtained were 980 articles, 11 articles were selected for review. Several articles compared the intensity of labor pain in the intervention group giving lavender aroma and without intervention and it was found that aromatherapy was an effective non-pharmacological pain management for reducing labor pain. The conclusion of this study is that giving lavender aroma is effective in reducing pain intensity during labor.